Military logistics as a research field of management and quality sciences - Jałowiec Tomasz; Pajka Aneta; WIĘCKOWSKI Bartłomiej (2023)
The scope of cognition of military logistics encompasses a wide variety of problems, among which priority is given to issues relating to the management and achieved quality of logistics processes. Over the past several decades, this issue has received a lot of attention, and the result of ongoing, interdisciplinary research is a significant body of international and domestic publications. Their careful analysis makes it possible to identify the key research fields of military logistics, which are the main subject of cognition within the framework of ongoing scientific research. Moreover, that the scope of the publications issued, and the scientific problems addressed in them, were in the past, and still invariably remain in close correlation to the socio-military-economic situation that took place in the period immediately preceding their publication. The aim of the article is Identification and assessment of the scope of contemporary cognition of military logistics in the area of management and quality sciences and bibliometric analysis of the phenomenon in question. The research problem taken up for solution was specified in the following form: what priority directions of scientific research dominate the development of military logistics in the area of management and quality sciences? A number of theoretical methods were used in the material, among which the leading ones were analysis and synthesis, abstraction and inference. On the basis of the analyses carried out, the article identifies connections, similarities and differences between the studied constructs, and formulates conclusions for further research using advanced methods of bibliometric analysis, i.e. the method of research profiling and methods that analyse the connections between publications